Clinical profiles, comorbidities and complications of type 2 diabetes mellitus in patients from United Arab Emirates. Issue 1 (8th August 2017) - Jelinek, Herbert F; Osman, Wael M; Khandoker, Ahsan H; Khalaf, Kinda; Lee, Sungmun; Almahmeed, Wael; Alsafar, Habiba S
Abstract : Objective: To assess clinical profiles of patients with type 2 diabetes in the United Arab Emirates (UAE), including patterns, frequencies, and risk factors of microvascular and macrovascular complications. Research design and methods: Four hundred and ninety patients with type 2 diabetes were enrolled from two major hospitals in Abu Dhabi. The presence of microvascular and macrovascular complications was assessed using logistic regression, and demographic, clinical and laboratory data were collected. Significance was set at p<0.05. Results: Hypertension (83.40%), obesity (90.49%) and dyslipidemia (93.43%) were common type 2 diabetes comorbidities. Most of the patients had relatively poor glycemic control and presented with multiple complications (83.47% of patients had one or more complication), with frequent renal involvement. The most frequent complication was retinopathy (13.26%). However, the pattern of complications varied based on age, where in patients <65 years, a single pattern presented, usually retinopathy, while multiple complications was typically seen in patients >65 years old. Low estimated glomerular filtration rate in combination with disease duration was the most significant risk factor in the development of a diabetic-associated complication especially for coronary artery disease, whereas age, lipid values and waist circumference were significantly associated with the development of diabetic retinopathy. Conclusions: Patients with type 2 diabetes mellitus in the UAE frequently present with comorbidities and complications. Renal disease was found to be the most common comorbidity, while retinopathy was noted as the most common diabetic complication. This emphasizes the need for screening and prevention program toward early, asymptomatic identification of comorbidities and commence treatment, especially for longer disease duration.